A Response to Recent Reanalyses of the National Reading Panel Report: Effects of Systematic Phonics Instruction Are Practically Significant - Stuebing, Karla K. (2008)
The authors examine the reassessments of the National Reading Panel (NRP) report (National Institute of Child Health and Human Development, 2000) by G. Camilli, S. Vargas, and M. Yurecko (2003); G. Camilli, P. M. Wolfe, and M. L. Smith (2006); and D. D. Hammill and H. L. Swanson (2006) that disagreed with the NRP on the magnitude of the effect of systematic phonics instruction. Using the coding of the NRP studies by Camilli et al. (2003, 2006), multilevel regression analyses show that their findings do not contradict the NRP findings of effect sizes in the small to moderate range favoring systematic phonics. Extending Camilli et al. (2003, 2006), the largest effects are associated with reading instruction enhanced with components that increase comprehensiveness and intensity. In contrast to Hammill and Swanson, binomial effect size displays show that effect sizes of the magnitude found for systematic phonics by the NRP are meaningful and could result in significant improvement for many students depending on the base rate of struggling readers and the size of the effect. Camilli et al. (2003, 2006) and Hammill and Swanson do not contradict the NRP report, concurring in supporting comprehensive approaches to reading instruction.